A review of recent research on the use of R1234yf as an environmentally friendly fluid in the organic rankine cycle - Garcia-Pabon, Juan; Méndez Méndez, Darío; Beltrán-Flores, Juan; Barroso Maldonado, Juan Manuel; Khosravi, Ali (My University, 2021)
ORC technology is one of the most promising technologies for the use of residual energy in the generation of electrical energy, offering simple and environmentally friendly alternatives. In this field, the selection of working fluids plays an important role in the operation of the cycle, whether in terms of the energy efficiency or the minimization of environmental impacts. Therefore, in this paper, a comprehensive review is presented on the use of R1234yf refrigerant and its mixtures as working fluids in ORC systems. These fluids are used in low- and medium-temperature applications for the use of residual energy generated from solar energy, geothermal energy, and internal combustion engines. It was concluded that R1234yf and its mixtures are competitive as compared with conventional refrigerants used in ORC. RESUMEN La tecnología ORC es una de las tecnologías más prometedoras para el aprovechamiento de energía residual en la generación de energía eléctrica, ofreciendo alternativas sencillas y respetuosas con el medio ambiente. En este campo, la selección de los fluidos de trabajo juega un papel importante en el funcionamiento del ciclo, ya sea en términos de eficiencia energética o de minimización de impactos ambientales. Por lo tanto, en este documento, se presenta una revisión exhaustiva sobre el uso del refrigerante R1234yf y sus mezclas como fluidos de trabajo en los sistemas ORC. Estos fluidos se utilizan en aplicaciones de baja y media temperatura para el aprovechamiento de energía residual generada a partir de energía solar, energía geotérmica y motores de combustión interna. Se concluyó que el R1234yf y sus mezclas son competitivos en comparación con los refrigerantes convencionales utilizados en ORC.
MDPI
Keywords: ORC System; R1234yf; Solar energy; geothermal energy; internal combustion enginer; Campus Mexicali